2013
DOI: 10.1111/pcn.12091
|View full text |Cite
|
Sign up to set email alerts
|

Temperature control can abolish anesthesia‐induced tau hyperphosphorylation and partly reverse anesthesia‐induced cognitive impairment in old mice

Abstract: Aims: Anesthesia is related to cognitive impairment and the risk for Alzheimer's disease. Hypothermia during anesthesia can lead to abnormal hyperphosphorylation of tau, which has been speculated to be involved in anesthesia-induced cognitive impairment. The aim of this study was to investigate whether maintenance of the tau phosphorylation level by body temperature control during anesthesia could reverse the cognitive dysfunction in C57BL/6 mice.Methods: Eighteen-month-old mice were repeatedly anesthetized du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…Cognitive impairment induced by anesthesia might be the most common type in postoperative cognitive disorder, which was found to influence signal pathways dysfunction, such as activation of GSK‐3β . This research was aimed to reveal the role of GSK‐3β inhibition on cognitive impairment induced by SEV anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive impairment induced by anesthesia might be the most common type in postoperative cognitive disorder, which was found to influence signal pathways dysfunction, such as activation of GSK‐3β . This research was aimed to reveal the role of GSK‐3β inhibition on cognitive impairment induced by SEV anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…Many rodent studies have demonstrated different experimental outcomes due to differences in body temperature under anesthesia, including studies of the heart, brain, liver, and urogenital system. 16,77,85,95,111,119,137 The technique used to measure body temperature is critical to the interpretation of an experiment, due to the heterogeneity of temperature in different locations of the animal's body, ranging from the temperature of the tail to the animal's true core temperature. The most traditional measurement of the core temperature is the use of direct rectal thermography by either a thermocouple or thermistor.…”
Section: Monitoring Body Temperature and Thermogenic Support Devicesmentioning
confidence: 99%
“…administration of insulin or deoxyglucose (Planel et al, 2004). Also, PP-Tau induction was suppressed in mice that were kept euthermic while under general anesthesia (Xiao et al, 2013).…”
Section: Introductionmentioning
confidence: 99%